Tumbuhan Berpotensi sebagai Pewarna Alami di Kawasan Air Terjun Sando Kota Lubuklinggau - Nopa Nopiyanti; Sepriyaningsih (Jurnal Biosilampari : Jurnal Biologi, 2024)
This study aim to explore the potential for using plants as natural dyes in the Sando waterfall area. This type of research is qualitative descriptive research. The method used in this research is a direct survey in the field by exploring the Sando Waterfall area. Data collection was carried out by making a brief description of the species and the habitat in which they were found. Species found are photographed to facilitate the identification process. Furthermore, the species found were identified using guidebooks, websites and journals about plants as natural dyes. From the search results, it was found that 10 types of plants have the potential to produce natural colors which are used as a source of dye for food, nail dye and fabric dye. There are 5 types of plants used as food coloring, namely guava (Psidium guajava), mulberry (Morus sp), turmeric (Curcuma domestica), telang (Clitoria ternatea), and suji (Pleomele angustifolia). One type of plant is used as a cosmetic/nail dye, i.e waru (Hibiscus tiliaceus). Meanwhile, for fabric dye, there are 5 types of plants, namely Harendong (Clidemia hirta), jengkol (Pithecellobium jiringa), papaya (Carica papaya), turmeric (Curcuma domestica), tarum (Indigofera tinctoria).